DISKRIMINASI TERHADAP ANAK TUNANETRA DALAM KELUARGA: KAJIAN PASTORAL KONSELING - Agnes Beatrix Jackline Raintung, Agnes Beatrix Jackline Raintung; Atalya Deharda Paraeng, Atalya Deharda Paraeng; Claudia Vain Manambe; Stela Binei, Stela Binei (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
Discrimination against blind children in the family is a complex problem and often occurs consciously and unconsciously which has an impact on the psychological and emotional development of children. This research aims to find out the forms of discrimination that occur, as well as their impact on blind children. The method used is descriptive qualitative, where researchers describe the forms of discrimination that occur, and how they affect children.